Analisis Perilaku Konsumsi Mahasiswa dalam Perspektif Ekonomi Perilaku pada Era Digital - Yusriza, Yusriza; Afhdal, Khairul; Syarifah Wilda, Naura; Amin, Muhammad (Cyber Media Indonesia, 2025)
The development of the digital era has transformed students’ consumption patterns, which are increasingly influenced by easy access to technology and exposure to promotions. The emerging issue is that consumption behavior is not always rational and tends to be shaped by psychological factors. This study aims to analyze students’ consumption behavior from a behavioral economics perspective in the digital era. This research employs a qualitative approach using a literature review method through the analysis of relevant scholarly sources. The findings indicate that students’ consumption behavior is influenced by cognitive biases such as present bias, loss aversion, and impulsive buying. The digital environment reinforces these tendencies through promotions, algorithms, and convenient payment systems. In conclusion, behavioral economics provides a more relevant framework for explaining students’ consumption dynamics in the digital era. Therefore, improving financial literacy is essential to encourage more rational consumption decisions. Abstrak Perkembangan era digital telah mengubah pola konsumsi mahasiswa yang semakin dipengaruhi oleh kemudahan akses teknologi dan paparan promosi. Permasalahan yang muncul adalah perilaku konsumsi yang tidak selalu rasional dan cenderung dipengaruhi faktor psikologis. Penelitian ini bertujuan menganalisis perilaku konsumsi mahasiswa dalam perspektif ekonomi perilaku pada era digital. Metode yang digunakan adalah kualitatif dengan pendekatan kajian pustaka melalui analisis literatur ilmiah yang relevan. Hasil penelitian menunjukkan bahwa perilaku konsumsi mahasiswa dipengaruhi oleh bias kognitif seperti present bias, loss aversion, dan pembelian impulsif. Lingkungan digital memperkuat kecenderungan tersebut melalui promosi, algoritma, dan kemudahan pembayaran. Artikel ini berkesimpulan, ekonomi perilaku lebih mampu menjelaskan dinamika konsumsi mahasiswa di era digital. Oleh karena itu, diperlukan peningkatan literasi keuangan agar keputusan konsumsi lebih rasional.